Knowledge, Perceptions, Challenges and opportunities in achieving sustainable coverage of mass drug administration towards the control and elimination of Schistosomiasis and Soil Transmitted Helminths in hard-to-reach communities of Ghana. - Akua Obeng Forson; Patrick F Ayeh-Kumi; Abdul Rahim Mohammed; Isaac Kwame Sraku; Gustavus Adolphus Myers-Hansen; Yaw Asare Afrane (PLoS Neglected Tropical Diseases)
Introduction In Ghana, schistosomiasis (SCH) and soil-transmitted helminths (STH) infections are of major public health problems in children. In the last decades, various interventions have been instituted by the Ghana Health Service (GHS) in collaboration with non-governmental organizations (NGOs) for the control and subsequent elimination of SCH and STH. However, these infections still remain common in both adults and children in many districts in Ghana. This study aimed to identify challenges in achieving sustainable coverage of mass drug administration for the control of STH and SCH and to explore opportunities to scale up its implementation among people living in hard-to-reach communities. Method Twelve focus group discussions (FGDs) with community members were conducted to access challenges to mass drug administration (MDA), and 20 in-depth interviews (IDIs) with key informants were conducted to access opportunities to optimize MDA to control and eliminate soil-transmitted helminth infections and schistosomiasis in hard-to-reach communities. Results Results showed participants held the correct notions of SCH and STH, and expressed willingness to participate in the MDA program. However, the lack of community drug distributors (CDDs) in the communities, inadequate and misleading information of MDA activities, and general concern about the adverse effects of MDA medications were some of the challenges identified to hinder MDA operations. Conclusion Transitioning from SCH and STH control to elimination goals requires intensive health education campaigns before MDA are conducted in hard-to-reach communities in Ghana. Furthermore, there is a need for political members and policymakers to collaborate in providing scarce and sanitary infrastructure and continuously provide disease-specific information to community members to address and dispel common misconceptions and anxieties regarding the transmission and treatment of SCH and STH.